2009
DOI: 10.1007/s00018-009-0185-1
|View full text |Cite
|
Sign up to set email alerts
|

MEPE evolution in mammals reveals regions and residues of prime functional importance

Abstract: In mammals, the matrix extracellular phosphoglycoprotein (MEPE) is known to activate osteogenesis and mineralization via a particular region called dentonin, and to inhibit mineralization via its ASARM (acidic serine-aspartate rich MEPE-associated motif) peptide that also plays a role in phosphatemia regulation. In order to understand MEPE evolution in mammals, and particularly that of its functional regions, we conducted an evolutionary analysis based on the study of selective pressures. Using 37 mammalian se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 55 publications
1
29
0
Order By: Relevance
“…S2A). This hypothesis is widely supported by several studies [11,41,42] and by our synteny analysis showing that in the G. gallus (also for M. gallopavo and T. guttata), OC-116 is localized in a mineralization-specific gene cluster (including bone sialoproteins and dentin matrix acidic phosphoprotein 1) on chromosome 4 and that this gene cluster is conserved between birds and mammals (Supplemental Fig. S2B).…”
Section: Ovocleidin-116supporting
confidence: 60%
See 1 more Smart Citation
“…S2A). This hypothesis is widely supported by several studies [11,41,42] and by our synteny analysis showing that in the G. gallus (also for M. gallopavo and T. guttata), OC-116 is localized in a mineralization-specific gene cluster (including bone sialoproteins and dentin matrix acidic phosphoprotein 1) on chromosome 4 and that this gene cluster is conserved between birds and mammals (Supplemental Fig. S2B).…”
Section: Ovocleidin-116supporting
confidence: 60%
“…The structure of OC-116 clearly shows that this gene belongs to the secretory calcium-binding phosphoprotein (SCPP) gene family, which is associated with the tissue mineralization in vertebrates [41]. In spite of the sequences of SCPP protein family being highly divergent, thanks to multiple sequence alignment based on exon conservation presented in Bardet's study [42], we were able to rebuild a phylogenetic tree. It seems to indicate a homology relationship between OC-116 and other SCPP proteins (Supplemental Fig.…”
Section: Ovocleidin-116mentioning
confidence: 93%
“…To validate the potential role of these mutations, hence to predict sensitive positions in MMP20, we analyzed a large set of representative mammalian lineages sequences, covering over 150 million years of evolution. This type of evolutionary analysis has been shown to be an efficient method to validate and predict disease-associated missense mutations (Delgado et al, 2007; Al Hashimi et al, 2009; Bardet et al, 2010; Silvent et al, 2014). This method is termed phylomedicine (Kumar et al, 2011), which is complementary to existing genetic diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our group successfully used this approach for predicting sensitive positions in various proteins of the secretory calcium-binding phosphoprotein family (26), and showed that missense mutations lead to genetic diseases. This approach was demonstrated on the following proteins: amelogenin (27), enamelin (28), matrix extracellular phospho-glycoprotein (29), amelotin (30), dentin matrix protein 1 (31), and ameloblastin. 6 Here, we perform the evolutionary molecular analysis of mammalian TNSALP to (i) highlight the functional or structural importance of various positions and domains; (ii) predict sensitive positions that should be responsible for a genetic disorder when substituted; and (iii) validate our predictions by using missense mutations reported in humans.…”
mentioning
confidence: 99%